Does SI Belong in Lower Secondary School? : An Exploratory Pre-study in a Swedish Socially Challenged Area - Fredriksson, Johan; Lindberg, Erik (Supplemental Instruction Journal, 2014)
Supplemental Instruction has worked very well in various settings all over the world. It should be of interest to see if SI works at earlier stages than tertiary education. There are examples of successful SI programs at upper secondary schools, but no reports from lower secondary schools. This study evaluates a pilot SI program in a 7th and a 9th grade class in a socially challenged area with regards to the general impression of SI, development of study strategies and general skills, motivation for further studies, and whether lower secondary school students would be interested to be SI Leaders themselves and, if so, why. Overall, questionnaires and student interviews indicate that SI seems to work in all evaluation areas. However, further extensive research is needed, and the authors suggest future areas to focus on.